Proceedings of the Web Conference 2021 2021
DOI: 10.1145/3442381.3449967
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Floor Plans into Hedonic Models for Rent Price Appraisal

Abstract: Online real estate platforms have become significant marketplaces facilitating users' search for an apartment or a house. Yet it remains challenging to accurately appraise a property's value. Prior works have primarily studied real estate valuation based on hedonic price models that take structured data into account while accompanying unstructured data is typically ignored. In this study, we investigate to what extent an automated visual analysis of apartment floor plans on online real estate platforms can enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Floor plan images have also proved to be useful for rent price prediction [12]- [14]. In [12], [13], it was demonstrated that conventional bag-of-features (BoFs) [15] has the potential to achieve lower-error prediction with smaller variance, although the contribution of BoFs was smaller than that of other apartment attribute information.…”
Section: B Real Estate Tasks Using Floor Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Floor plan images have also proved to be useful for rent price prediction [12]- [14]. In [12], [13], it was demonstrated that conventional bag-of-features (BoFs) [15] has the potential to achieve lower-error prediction with smaller variance, although the contribution of BoFs was smaller than that of other apartment attribute information.…”
Section: B Real Estate Tasks Using Floor Planmentioning
confidence: 99%
“…In [12], [13], it was demonstrated that conventional bag-of-features (BoFs) [15] has the potential to achieve lower-error prediction with smaller variance, although the contribution of BoFs was smaller than that of other apartment attribute information. In [14], image features were applied to hedonic price models [16] to predict the apartment rent price after controlling for locational and structural characteristics of an apartment.…”
Section: B Real Estate Tasks Using Floor Planmentioning
confidence: 99%
“…, 2016). In the real estate field, Solovev and Pröllochs (2021) choose a pretrained ConvNet to predict apartment rent prices using pictures of the floor plans as the input. Shen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors have used them as additional factors to textual features for the development of different types of AVMs based on HPM, ANN, and different ML-based techniques. Some of them have also evaluated the efficacy of adding such visual features to other textual value-related factors and indicated the capabilities of visual features in increasing the accuracy of the AVMs (De Nadai and Lepri, 2018;Helbich et al, 2013;Kostic and Jevremovic, 2020;Law et al, 2019;Lee and Park, 2020;Liu et al, 2018;Muhr et al, 2017;Nouriani and Lemke, 2022;Poursaeed et al, 2018;Solovev and Pröllochs, 2021).…”
Section: Visual Featuresmentioning
confidence: 99%